RET 647 Group Assignment: The Dough Knot / Afiq Irfan Mahazim, Fatin Nadhirah Amry, Nur Athirah Bahaman ... [et al.] - Mahazim, Afiq Irfan; Amry, Fatin Nadhirah; Bahaman, Nur Athirah; Mohd Zulkaflee, Nur Izzah; Salleh, Nur Nabila; Abd Kahar, Nurhafizah; Ruah, Nurulnabilah (2021)
Our main product is donuts with various flavours such as Peanut Butter Glaze with 100% premium nuts as the toppings. Next is Overload Vanilla Oreo, a combination of vanilla with oreo cookies for customers who love cookie cream taste like. Then, The Dough Knot also has coffee edition donuts which are Mocha Glaze, Macchiato Irish and Latte Italiano donuts for coffee lovers. A donut will not be complete without the main and classic flavours which are Chocolate Choco, Strawberry Jelly and Shredded Cheese donuts. Lastly we also have Salted Caramel Peanuts donuts. For special edition flavour, we have matcha green tea, durian fillings, mango fillings and also we have blueberries edition. All the ingredients that we use to produce the donuts are premium.